Kemas Ulang Informasi Ragam Alat Musik Tradisional Minangkabau sebagai Koleksi Perpustakaan Sekolah (Studi Kasus di SD Negeri 33 Rawang Barat, Padang) - Puti Anjani, Della; Primadesi, Yona (Departemen Informasi Perpustakaan dan Kearasipan, 2025)
The writing of this article is motivated by the absence of a collection on traditional musical instruments in the library of SD Negeri 33 Rawang Barat, Padang City. This project aims to describe: (1) the process of creating an information repackaging of various Minangkabau traditional musical instruments as a library collection for SD Negeri 33 Rawang Barat; and (2) the trial results of the information repackaging of various Minangkabau traditional musical instruments as a library collection for SD Negeri 33 Rawang Barat. This final project was carried out using a descriptive method, with data collection techniques through interviews, observation, and literature study. Based on the completion of this final project, the following results were obtained. First, the creation of the information repackaging can be carried out in six stages: (1) determining the knowledge or specific topic based on the target users; (2) identifying users’ needs through interviews, questionnaires, or observation; (3) selecting a packaging format that suits the users’ needs and interests; and (4) determining the channel for information dissemination. Second, the trial of the information repackaging product as a school library collection was conducted using trial questionnaires divided into two parts: (1) the information aspect trial questionnaire obtained a score of 100% with an “Excellent” rating (A); and (2) the physical aspect trial questionnaire obtained a score of 95.83% with an “Excellent” rating (A). Overall, the final result shows that the appearance of the information repackaging about various Minangkabau traditional musical instruments in the library of SD Negeri 33 Rawang Barat, Padang has been successfully implemented with excellent results.